Tectonic evolution of the Qingshuihe Basin since the Late Miocene: Relationship with north‐eastward expansion of the Tibetan Plateau. (13th October 2019) - Tian, Jingxiong; Li, Mingtao; Liang, Zhirong; Li, Liming; Yan, Guoxiang; Lu, Maoxin; Tan, Zhen
Abstract : Southwest Ningxia is located at the tectonic and geographical north‐eastern edge of the Tibetan Plateau and is an ideal site for studying continental dynamics and plateau building. The Southern Ningxia Arc Tectonic Belt (SNATB) formed during the Cenozoic period as a result of the collision between India and Eurasia and was affected by the Tibetan Plateau uplift. However, the upward growth and expansion processes of the SNATB remain unclear. We investigated the Qingshuihe Basin (a Late Cenozoic basin located between the Tianjingshan and Qingshuihe faults in the north‐eastern SNATB) using field geological surveys combined with borehole, high‐density resistivity, and optically stimulated luminescence dating. Four distinct stages in the tectonic evolution of the Qingshuihe Basin since the Late Miocene are identified, corresponding to four tectonic events in the local region influenced by the Tibetan Plateau expansion. First, the Late Miocene experienced several significant events, including tectonic stress field transitions, sedimentary hiatus, and sudden environmental changes, which may have been the first local tectonic activity due to the north‐eastward expansion of the Tibetan Plateau. Second, the Early–Middle Pleistocene growth strata in the Hejiakouzi valley (controlled by the Hejiakouzi anticline and Tianjingshan Fault) suggest that the basin‐range‐style tectonic features were basically formed in the SNATB. Third, geological investigations of lacustrine sedimentation reveal that two palaeolakes were present during the Late Pleistocene. Significant phase transitions and a sedimentary hiatus during the Late Pleistocene in the lake formations indicate a transformation of the sedimentary environment, which marked the beginning of the left‐lateral strike‐slip of the Tianjingshan Fault. Finally, the broad distribution of second‐level river terraces along the banks of the Qingshuihe and other seasonal rivers close to the Tianjingshan indicate the effect of the north‐eastward expansion of the Tibetan Plateau on the local tectonic evolution. We elucidate the stratigraphy, major unconformities, and river terraces formed since the Late Miocene in the Qingshuihe Basin, providing important information regarding the tectono‐topographical‐sedimentary system.